Nanofabrication and Demonstration of a Direct‐Write Microevaporator - Xella Doi; Pavani Vamsi Krishna Nittala; Brian Fu; Kyaw Zin Latt; Suryakant Mishra; Luke Silverman; Linus Woodard; Ralu Divan; Supratik Guha (Small Science, 2024)
Direct‐write vapor deposition is a new technique that would enable one‐step 3D maskless nanofabrication on a variety of substrates. A novel silicon chip‐based microevaporator is developed that allows evaporant to exit through 2000–300 nm nozzles while held at distances comparable to the nozzle diameter from the substrate by a three‐axis nanopositioning stage in vacuum. This results in a localized deposition on the substrate, which may be scanned relative to the substrate to produce direct‐write patterns. The performance of the microevaporator is tested by creating localized depositions of various materials and the line‐writing potential is demonstrated. The relationship between linewidth and source‐to‐substrate distance is investigated by the application of Knudsen's cosine law and Monte‐Carlo simulations, and then utilized to approximate the source‐to‐substrate distance from performed depositions.